STRATEGI PROGRAM KAMPANYE DESAK ANIES PADA PEMILIHAN PRESIDEN 2024 - Jilan Aghashi Ihasof; nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
This study aims to analyze the Desak Anies campaign program strategy in the 2024 Presidential Election. The research is motivated by the emergence of innovative political campaign approaches that utilize dialogue-based communication to strengthen interaction between candidates and the public. The scope of this study focuses on the formulation and implementation of the Desak Anies program as part of the campaign strategy of Anies Baswedan and Muhaimin Iskandar in the 2024 Presidential Election. This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The analysis is based on Antar Venus's campaign strategy theory. The findings indicate that the Desak Anies campaign program was designed through the development of substantive political messages, audience targeting focused on young voters, the utilization of digital media, and the implementation of an open-dialogue format that enabled direct interaction between candidates and the public. The program served not only as a medium for delivering political visions and missions but also as a platform for public participation in the campaign process. The study concludes that Desak Anies represents a campaign strategy that integrates direct communication and digital media to enhance public engagement in the 2024 Presidential Election.